Ontogeny of ependymoglial cells lining the third ventricle in mice - Lopez-Rodriguez, David; Rohrbach, Antoine; Lanzillo, Marc; Gervais, Manon; Croizier, Sophie; Langlet, Fanny (Frontiers in Endocrinology, 2023)
During hypothalamic development, the germinative neuroepithelium gives birth to diverse neural cells that regulate numerous physiological functions in adulthood. Here, we studied the ontogeny of ependymal cells in the mouse mediobasal hypothalamus using the BrdU approach and publicly available single-cell RNAseq datasets. We observed that while typical ependymal cells are mainly produced at E13, tanycyte birth depends on time and subtypes and lasts up to P8. Typical ependymocytes and β tanycytes are the first to arise at the top and bottom of the dorsoventral axis around E13, whereas α tanycytes emerge later in development, generating an outside-in dorsoventral gradient along the third ventricle. Additionally, α tanycyte generation displayed a rostral-to-caudal pattern. Finally, tanycytes mature progressively until they reach transcriptional maturity between P4 and P14. Altogether, this data shows that ependyma generation differs in time and distribution, highlighting the heterogeneity of the third ventricle.